Unsur-unsur Filsafat Manusia yang Terkandung dalam Pemikiran Filsafat Cina dan Manfaatnya bagi Peningkatan Sumber Daya Insani - Lasiyo, Lasiyo (Jurnal Filsafat "WISDOM", 1999)
The purpose of this study is to find out the elements of Philosophical Antropology in Chinese Philosophy and its controbution to improve the quality of human resource in relation to clarify and to enrich the matter of this subject, which usually more emphasized on Western philosophy than Eastern philosophy.The research was conducted by studying literature and data collected from primary and secondary source, which have been published or not. Hermeneutics theory, comparative study, and interpretation method were used in the analysis of the data collected. Conclusion are made base on logical thinking.The result of this work is that elements of Philosophical Antropology in Chinese Philosophy could be analyzed from the philosophy of Confucianism, Legalism, Buddism, and Taoism. Confucianism concered on human nature, existence, and dimensions, which consist of social, cosmic, transcendental, and historical dimensions. Legalism emphasized every human being have Buddha nature, while Taoism advised life in harmony with the nature like a yin yang principles. In improving the quality of human resource showed that everyone can be developed through education and environment. Creative thinking and working culture are necessary to improved in achieving the quality of work life.